the Analisis Kemampuan Literasi Numerasi Siswa Ditinjau dari Gaya Belajar pada Materi Statistika - Dwi Imrianti Zahrah; Noviana Dini R; Nur Asiyah; M Nizaruddin (Departement of Mathematics Education, 2024)
This research aims to analyze students' numeracy literacy skills in solving statistics problems in terms of learning style. This type of research is a qualitative study involving one subject for each visual, auditory and kinesthetic learning style. This research data was taken through a learning style questionnaire, numeracy literacy skills test and interviews. Validity of data using triangulation and analysis techniques used by reducing data, presenting data and drawing conclusions. The results of the research show that students with a visual type learning style are able to understand or write down what information is known and what information is asked about the problem, are able to present the information obtained in tabular form, are able to determine and use appropriate arithmetic operations in solving the given problem, able to conclude the results of problem solving. Students with an auditory type learning style are able to understand or write down what information is known and what information is asked about the problem and are able to present the information obtained again in tabular form. Students with a kinesthetic type learning style are able to understand or write down what information is known and what information is asked about the problem.